Improvement of SCD morbimortality in children: experience in a remote area of an African country - Benoît Mukinayi Mbiya; Didier Kalenda Kalombo; Yannick Nkesu Mukendi; Valery Daubie; John Kalenda Mpoyi; Parola Mukendi Biboyi; Ghislain Tumba Disashi; Béatrice Gulbis (BMC, 2021)
Abstract Background Sickle cell disease (SCD) is a public health problem in the Democratic Republic of Congo. While reference sickle cell centers have been implemented in capital cities of African countries and have proven to be beneficial for SCD patients. In the Democratic Republic of Congo, they have never been set up in remote areas for families with low or very low sources of income. Method A cohort of 143 children with SCD aged 10 years old (IQR (interquartile range): 6-15 years) (sex ratio male/female = 1.3) were clinically followed for 12 months without any specific intervention aside from the management of acute events, and then for 12 months with a monthly medical visit, biological follow-up, and chemoprophylaxis (folic acid/penicillin), adequate fluids and malaria prevention. Results The median age of patients at the diagnosis of SCD was 2 years (IQR: 1-5). The implementation of standardized and regular follow-ups in a new sickle cell reference center in a remote city showed an increase in the annual mean hemoglobin level from 50 to 70 g/L (p = 0.001), and a decrease in the lymphocyte count and spleen size (p < 0.001). A significant decrease (p < 0.001) in the average annual number of hospitalizations and episodes of vaso-occlusive crises, blood transfusions, infections, and acute chest syndromes were also observed. Conclusions The creation of a sickle cell reference center and the regular follow-up of children with sickle cell disease are possible and applicable in the context of a remote city of an African country and represent simple and accessible measures that can reduce the morbimortality of children with sickle cell disease.